Discovery of diversity in xylan biosynthetic genes by transcriptional profiling of a heteroxylan containing mucilaginous tissue - Jensen, Jacob K.; Johnson, Nathan; Wilkerson, Curtis G. (Frontiers in Plant Science, 2013)
The exact biochemical steps of xylan backbone synthesis remain elusive. In Arabidopsis, three non-redundant genes from two glycosyltransferase (GT) families, IRX9 and IRX14 from GT43 and IRX10 from GT47, are candidates for forming the xylan backbone. In other plants, evidence exists that different tissues express these three genes at widely different levels, which suggests that diversity in the makeup of the xylan synthase complex exists. Recently we have profiled the transcripts present in the developing mucilaginous tissue of psyllium (Plantago ovata Forsk). This tissue was found to have high expression levels of an IRX10 homolog, but very low levels of the two GT43 family members. This contrasts with recent wheat endosperm tissue profiling that found a relatively high abundance of the GT43 family members. We have performed an in-depth analysis of all GTs genes expressed in four developmental stages of the psyllium mucilagenous layer and in a single stage of the psyllium stem using RNA-Seq. This analysis revealed several IRX10 homologs, an expansion in GT61 (homologs of At3g18170/At3g18180), and several GTs from other GT families that are highly abundant and specifically expressed in the mucilaginous tissue. Our current hypothesis is that the four IRX10 genes present in the mucilagenous tissues have evolved to function without the GT43 genes. These four genes represent some of the most divergent IRX10 genes identified to date. Conversely, those present in the psyllium stem are very similar to those in other eudicots. This suggests these genes are under selective pressure, likely due to the synthesis of the various xylan structures present in mucilage that has a different biochemical role than that present in secondary walls. The numerous GT61 family members also show a wide sequence diversity and may be responsible for the larger number of side chain structures present in the psyllium mucilage.